Bilateral vs Unilateral Minimally Invasive Hallux Valgus Surgery: A Propensity Matched Case-Control Study with 2 Year Clinical Patient Reported Outcomes. Issue 1 (January 2022) - Gordon, David; Crooks, Sophie A.; Lewis, Thomas L.; Ray, Robbie
Category: Bunion; Midfoot/Forefoot Introduction/Purpose: Hallux valgus deformity correction using a third-generation Minimally Invasive Chevron Akin osteotomy technique (MICA) is becoming increasingly popular. There is limited patient reported outcome measure (PROM) outcomes for patients undergoing bilateral hallux valgus corrective MICA surgery during a single operative case. Methods: Between July 2014 and May 2018, 59 consecutive patients comprising 118 feet underwent bilateral MICA in a single operative case. 1:1 propensity score matching based on preoperative PROM assessment, age, and radiographic deformity data was carried out to match each foot in the bilateral cohort with 118 feet who had undergone unilateral MICA. The primary outcome measure was the Manchester-Oxford Foot Questionnaire (MOXFQ) which was prospectively measured pre-operatively, six months and two years post-operatively. Secondary outcomes included complication rates and radiographic deformity correction with regards to the hallux valgus angle (HVA) and inter-metatarsal angle (IMA). Results: At minimum 2 year follow up, the MOXFQ post-operative scores had significantly improved for every domain (p <0.001) in both unilateral and bilateral cohorts compared to pre-operative assessment. For all domains of the MOXFQ, there was no statistically significant difference in 6 month or two year outcomes between patients undergoing bilateral and unilateral MICA surgery (p >0.05 for all outcome measures). There was no statistically significant difference between the two cohorts in complication rate (p=>0.05) or post-operative IMA or HVA (p >0.05). Conclusion: This study demonstrates that there is no significant difference in patient reported outcome measured at two year follow-up between patients who underwent bilateral versus unilateral MICA. This study should reassure surgeons who perform bilateral hallux valgus surgery in a single case that, in the medium-term, there is no difference in clinical or radiographic PROMs compared to unilateral surgery. There are potentially positive health economic benefits of performing bilateral surgery in a single sitting if clinically indicated.